Dynamic variable volume sampling method for determining mass emissions of polluting substances with exhaust gases - Klimenko, Oleksiy (Eastern-European Journal of Enterprise Technologies, 2020)
The results of the development and research of a promising full-flow dynamic method of variable volume sampling to determine in laboratory conditions the values of mass emissions of pollutants from the exhaust gases of automobile engines are presented. Emissions are determined by the test procedures for complete vehicles in driving cycles, or separately of their engines in motor test cycles. Current mass emissions of pollutants are calculated from time-synchronized instantaneous concentrations and instantaneous flow rates of the mixture of exhaust gases and air. In the mixing chamber, which serves the exhaust gases and air, also serves calibration gas mixture with a flow rate that is changed in accordance with the periodic function. This is used to determine the transfer functions of the inverse calculation of the instantaneous flow rate of the mixture of exhaust gases and air, and the current values of the concentrations of pollutants at the time of sampling. Mass emissions of gaseous pollutants are calculated as the difference between the total mass emissions of pollutants and the mass emissions of pollutants that are added with the flow of the calibration gas mixture. The performance of the dynamic full-flow variable-volume sampling method is proved by comparing the calculated (carbon balance method) and directly measured fuel consumption by cars in driving cycles. The difference between the directly measured and calculated (for certain mass emissions of pollutants) fuel consumption does not exceed±3.5 %. This is a satisfactory result, taking into account, in particular, the measurement uncertainty in the dynamics of rapidly changing concentrations of pollutants, diluted exhaust gas flow rate, fuel consumption, and the determination of carbon content in the fuel. Fundamentally new possibilities have been obtained for measuring the mass specific emissions of pollutants by forced-ignition engines and modern diesel engines (Euro-6 environmental class) and promising low-emission vehicles.